Level of Knowledge, Attitude, and Practice of Pregnant Women on Antenatal Care in Amatere Health Center, Massawa, Eritrea: A Cross-Sectional Study, 2019 - Hailemichael Gebremariam; Berhe Tesfai; Seltene Tewelde; Yonas Kiflemariam; Fitsum Kibreab (Hindawi Limited, 2023)
Background. Proper antenatal care is one of great means of reducing maternal and child morbidity and mortality. However, determining level of knowledge and practice is vital, and the objective of this study was to evaluate this gap among pregnant women in Amatere Health Center, Massawa city, Eritrea, 2019. Methods. A cross-sectional study with systematic sampling was conducted. All pregnant mothers who were resident of Massawa city and visiting Amatere Health Center for their current pregnancy were included in the study. An interviewer-administered structured questionnaire was used as data collection tool. Results were presented using descriptive statistics, percent, and frequencies. Results. A total of 289 pregnant mothers were enrolled in the study with a mean age of 27.7 years. Most mothers reported that high blood pressure (92.4%), maternal smoking (97.6%), alcohol consumption (97.2%), infection (92.7%), and medicines (98.3%) had affected fetal growth during pregnancy. Practically, two-thirds (59.4%) of the mothers were visiting the health facility during the first three months of their pregnancy. Majority of mothers had good knowledge (84.1%) and attitude (99%), but they had low level of practice (45%). Marital status, occupation, gravidity, and parity had showed statistically significant association to their comprehensive knowledge (p<0.001). And their gravidity (p<0.003) and parity (p<0.001) had also showed statistically significant association to their level of practice. Conclusion. Even though majority of the pregnant mothers had high level of knowledge and attitude, their practice towards ANC was relatively low. Age, marital status, and occupation showed statistically significant association to their comprehensive knowledge. Moreover, multiparous and multigravida mothers were having higher level of knowledge and practice on antenatal care. Enhancing community awareness on early starting of antenatal care and improving their practice through proper counseling are highly recommended.